Dielectric, electro-optical and viscoelastic properties of nematic phase driven by hydrogen-bonding between cyano group and fluoroalkoxybenzoic acid. Issue 14 (14th November 2022) - Meddeb, Bassem; Saadaoui, Lotfi; Guesmi, Ahlem; Ben Hamadi, Naoufel; Soltani, Taoufik
ABSTRACT: Hydrogen-bonded liquid crystals (HBLC) formed by mixing 4-alcyloxy-2-fluorobenzoic acid (nOBAF) and the 4-pentyl-4-biphenylcarbonitrile (5CB) at (1:1), (1:3) and (3:1) (mol/mol) ratios have been investigated. Four HBLC series are prepared by changing the carbon chain length from 7 to 10 designated 5CB/nOBAF. The fluorobenzoic acids (nOBAF) are the proton donors while the pyridine unit (5CB) is the proton acceptors. Thermal behaviour and phase diagrams of the individual series have been established using differential scanning Calorimetry (DSC) and polarising optical microscopy (POM). It was found that all complexes exhibit nematic (N) and smectic G (SmG) phases. For the nematic phase, the dielectric anisotropy was increased while the thresholds voltage was decreased. This can be explained by the strong longitudinal dipole moment of the nematic phase compared to the nOBAF compounds. Furthermore, as the alkoxy chain length increases, the birefringence, response time, rotational viscosity, and splay elastic constant all decrease by the way of the reduction of the order parameter for the longer chains. In addition, hydrogen-bonded proton transfer between cyano and carboxylic acid groups have been explored by Fourier transform infrared spectroscopy (FTIR) for the first time. GRAPHICAL ABSTRACT: uf0001